Geomorfologia como base de análise ambiental integrada para o planejamento municipal: estudo de caso de Itabirito-MG - Paula Márcia Brasil Garcia (2019)
The growth of cities without adequate planning can lead to áreas potentially at risk for mass movements and accelerated erosion, in addition to vários level of problems, as is happening in considerable portions of urban areas in the underdeveloped and depeloping world. This suggests that the environmental issue does not receive due attention in the vários types and levels of territorial planning. The municipality of Itabirito is part of this perspective. Located in the Metropolitan Mesoregion of Belo Horizonte – MG, it integrates, together with three Other municipalities, Mariana, Diogo de Vasconscelos and Ouro Preto, the Microregion of Ouro Preto. The objective of this work is to presente approaches based on environmental analysis, focusing on geomorphology, combined with geotechnologies to guide and support the development of Master Plans and Other instruments of territorial planning.The geomorphological analyzes allowed us to understand some of the effects and responses of the physical environment resulting from the city’s urabnization process in wich the environmental variables were not adequately considered.It was possible to observe in several places that, combined with the natural conditions of susceptibility, the anthropogenic action has been changing the natural dynamics of the study área, contributing to the intensification of slope processes (concentrated runoff), leading to accelerated erosion and affecting river dynamics. The multicriteria analysis techniques were used to analyze the municipal zoning regarding urban expansion areas and identification of growth vectors. From the identification of suitable places for occupation from de geomorphological and enviromenmental point of view, it was possible to proceed with the delimitation of the zones as well as their guidelines for use and occupation, since places identified as having low aptitude for occupation, refer that, onde occupied, start to pose risks both to life and the environment in general, also increasing the possibilities of material losses related to civil construction.